Insuring Peace: Index-Based Livestock Insurance, Droughts, and Conflict - Kai Gehring; Paul Schaudt (The Quarterly Journal of Economics, 2026)
Abstract We provide quasi-experimental evidence of how an innovative market-based solution using remote-sensing technology can mitigate drought-induced conflict. Droughts are a major driver of conflict in Africa, particularly between transhumant pastoralists and sedentary farmers. Index-Based Livestock Insurance (IBLI), a program piloted in Kenya, provides automated, preemptive payouts to pastoralists affected by droughts. Combining variation in rainfall and the staggered rollout of IBLI in Kenya over 2000–2020, we find that IBLI strongly reduces drought-induced conflict. Key mechanisms include a reduction in herd sizes, as well as income smoothing and asset price stabilization, contributing to an overall reduced migratory pressure for pastoralists. Our study suggests that market-based solutions are a scalable, cost-effective pathway to mitigate conflict, complementing political solutions such as power-sharing agreements and institutional reforms.